Construction of a Prognostic Risk Prediction Model for Obesity Combined With Breast Cancer - Sun, Na; Ma, Dandan; Gao, Pingping; Li, Yanling; Yan, Zexuan; Peng, Zaihui; Han, Fei; Zhang, Yi; Qi, Xiaowei (Frontiers in Endocrinology, 2021)
The improvement in the quality of life is accompanied by an accelerated pace of living and increased work-related pressures. Recent decades has seen an increase in the proportion of obese patients, as well as an increase in the prevalence of breast cancer. More and more evidences prove that obesity may be one of a prognostic impact factor in patients with breast cancer. Obesity presents unique diagnostic and therapeutic challenges in the population of breast cancer patients. Therefore, it is essential to have a better understanding of the relationship between obesity and breast cancer. This study aims to construct a prognostic risk prediction model combining obesity and breast cancer. In this study, we obtained a breast cancer sample dataset from the GEO database containing obesity data (determined by the body mass index (BMI)). A total of 1174 genes that were differentially expressed between breast cancer samples of patients with and without obesity were screened by the rank-sum test. After weighted gene co-expression network analysis (WGCNA), 791 related genes were further screened. Relying on single-factor COX regression analysis to screen the candidate genes to 30, these 30 genes and another set of TCGA data were intersected to obtain 24 common genes. Finally, lasso regression analysis was performed on 24 genes, and a breast cancer prognostic risk prediction model containing 6 related genes was obtained. The model was also found to be related to the infiltration of immune cells. This study provides a new and accurate prognostic model for predicting the survival of breast cancer patients with obesity.